2020
DOI: 10.31487/j.cor.2020.04.12
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Predictive Value of the Tumor-Stroma Ratio in STAGE II Colon Cancer

Abstract: Background: Tumor-stroma ratio (TSR) is an independent prognosticator in colon cancer. Objective: We set out to investigate the predictive power, as well as to validate the prognostic power of TSR in stage II colon cancer patients. Better identification of patients who could benefit from adjuvant chemotherapy remains an important issue in stage II disease. Methods: TSR was microscopically determined on haematoxylin and eosin-stained primary tumor tissue slides of 212 patients who received either adjuvant chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…On the other hand, a study published by Roseweir et al, which had a total of 14% low TSR in study population, noted statistically significantly worse outcome for DFS among low TSR subjects. The other three studies (5,26,28) have showed significant association of low TSR with worse prognosis for outcome DFS in stage II CRC. In the stage III CRC, two studies (5,19) showed that low TSR is associated with worse outcome for DFS and OS.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…On the other hand, a study published by Roseweir et al, which had a total of 14% low TSR in study population, noted statistically significantly worse outcome for DFS among low TSR subjects. The other three studies (5,26,28) have showed significant association of low TSR with worse prognosis for outcome DFS in stage II CRC. In the stage III CRC, two studies (5,19) showed that low TSR is associated with worse outcome for DFS and OS.…”
Section: Discussionmentioning
confidence: 95%
“…Nine studies reported on the use of chemotherapy for treatment, with five ( 18 , 19 , 25 , 28 , 30 ) describing adjuvant chemotherapy, two ( 17 , 26 ) describing surgery combined with chemotherapy, one describing chemotherapy and rofecoxib ( 5 ), and one describing only chemotherapy ( 16 ). One study ( 20 ) documented radiotherapy in conjunction with chemoradiotherapy ( 27 ), while another study ( 24 ) recommended neo-adjuvant radiotherapy in conjunction with radiotherapy as a treatment option.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies reported on the use of chemotherapy for treatment, with five (18, 19, 25, 28, 30) describing adjuvant chemotherapy, two (17,26) describing surgery combined with chemotherapy, one describing chemotherapy and rofecoxib (5), and one describing only chemotherapy (16). One study (20) documented radiotherapy in conjunction with chemoradiotherapy (27), while another study (24) recommended neo-adjuvant radiotherapy in conjunction with radiotherapy as a treatment option.…”
Section: Study Characteristicsmentioning
confidence: 99%